2014
DOI: 10.1007/s00441-014-1821-0
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of pulmonary endothelial barrier function in acute inflammation: mechanisms and therapeutic perspectives

Abstract: The lungs provide a large inner surface to guarantee respiration. In lung alveoli, a delicate membrane formed by endo- and epithelial cells with their fused basal lamina ensures rapid and effective gas exchange between alveolar and vascular compartments while concurrently forming a robust barrier against inhaled particles and microbes. However, upon infectious or sterile inflammatory stimulation, tightly regulated endothelial barrier leakiness is required for leukocyte transmigration. Further, endothelial barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 195 publications
(236 reference statements)
3
54
0
1
Order By: Relevance
“…One possible explanation might be that during CPB procedures, direct contact of blood with pipeline, ischemia/reperfusion, and other anesthesia and surgical factors might induce systemic inflammatory response at the surface-blood interface or during ischemic reperfusion, and lead to the production of inflammatory mediators (Xu et al, 2011;Kortekaas et al, 2014). The accumulation and activation of inflammatory mediators and neutrophils, in turn, play leading roles in increasing the pulmonary endothelial permeability; hence, damage to lung tissue structure is a critical event for initiating an pulmonary edema, atelectasis, or hypoxemia postoperatively (Grommes and Soehnlein, 2011;Muller-Redetzky et al, 2014). Sevoflurane could successfully decrease the production of inflammatory mediators, which is largely attributed to the mechanism of sevoflurane in blocking the activation of the complement system and downregulating the generation of inflammatory mediators, and thereby help to reduce inflammatory response caused by CPB (Schmid et al, 2012;Watanabe et al, 2013;Aguado et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation might be that during CPB procedures, direct contact of blood with pipeline, ischemia/reperfusion, and other anesthesia and surgical factors might induce systemic inflammatory response at the surface-blood interface or during ischemic reperfusion, and lead to the production of inflammatory mediators (Xu et al, 2011;Kortekaas et al, 2014). The accumulation and activation of inflammatory mediators and neutrophils, in turn, play leading roles in increasing the pulmonary endothelial permeability; hence, damage to lung tissue structure is a critical event for initiating an pulmonary edema, atelectasis, or hypoxemia postoperatively (Grommes and Soehnlein, 2011;Muller-Redetzky et al, 2014). Sevoflurane could successfully decrease the production of inflammatory mediators, which is largely attributed to the mechanism of sevoflurane in blocking the activation of the complement system and downregulating the generation of inflammatory mediators, and thereby help to reduce inflammatory response caused by CPB (Schmid et al, 2012;Watanabe et al, 2013;Aguado et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…4D). Because endothelial barrier dysfunction often correlates with the severity of lung inflammation (28) we reasoned that vascular permeability might also be increased in lungs of C1q Ϫ/Ϫ mice after LPS or HCl administration. Consistent with this line of reasoning, we found that total protein concentration (Fig.…”
Section: C1q Deficiency Exacerbates Lps and Hcl-induced Lungmentioning
confidence: 99%
“…It is generally accepted that ALI involves inflammation injury to the alveolar-capillary barrier, resulting in increased lung permeability, accumulation of protein-rich pulmonary edema fluid, neutrophil entrapment and activation in the airspaces [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial toxins rapidly compromise endothelial cell function, leading to disruption of endothelial barrier integrity and subsequent pulmonary hyperpermeability [6,7]. Based on these facts, it is reasonable that protecting endothelial function could be a novel therapeutic strategy [2]. However, no specific pharmacologic therapy to date is available to improve endothelial function in the treatment of ALI.…”
Section: Introductionmentioning
confidence: 99%